Data from manuscripts "Reconciling equatorward migration of Southern Ocean fronts with minor Antarctic ice volume change during Miocene cooling" and "Southern Ocean control on atmospheric CO2 changes across late-Pliocene Marine Isotope Stage M2" by Suning Hou and others - Hou, Suning (Zenodo, 2024)
Datasets published along the manuscript " Reconciling equatorward migration of Southern Ocean fronts with minor Antarctic ice volume change during Miocene cooling " (published), and " Southern Ocean control on atmoshpheric CO2 changes across late-Pliocene Marine Isotope Stage M2 " (submitted) 6 datasets, all generated from ODP Site 1168, are submitted: data1 raw palynological counts data2 relative abundance of dinocyst ecogroups data3 dinocyst-based SST reconstructions data4 clumped isotope-based BWT reconstructions (raw clumped isotope data is deposited elsewhere) calibration: Δ 47=( 0. 0397 ± 0 . 0011) * 10e 6/ T 2 +( 0.1 518 ± 0 . 0128) (Temperature in K) data5 benthic foraminifer stable isotopes data6 bulk stable isotopes Data 1, 2 and 5 are updated with the new data from the Pliocene;. Depth is plotted in meters below sea floor; sample depths are derived from the Ocean Drilling Program Age is in millions of years, calibrated to the Geologic Time Scale 2020.